(untitled) (Research, Society and Development, 2022)
The aim of this study is to summarize the evidence in the literature about the effect of probiotics on glycemic control in patients with type 2 diabetes mellitus (T2DM). This is an integrative literature review to answer the question: “What is the evidence on the use of probiotics to reduce fasting glucose and/or glycated hemoglobin and/or insulin resistance in people with T2DM”. The search was performed in the Medline-PubMed, Cochrane Library and Bireme databases using descriptors combined using the OR and AND operators. Randomized clinical trials performed with adult humans diagnosed with T2DM and which evaluated at least one of the outcomes of interest were included. The search resulted in 207 articles, of which 14 were included. The duration of the intervention ranged from 6 weeks to 6 months, the number of strains from 1 to 14, the daily dose from 106 to 1010 CFU. Most studies included Lactobacillus and Bifidobacterium. The species and strains that appeared the most were Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium lactis and Streptococcus Thermophilus. It is suggested that the use of probiotics may be a strategy for managing T2DM, as most studies have shown a positive effect on at least one of the parameters.